Direction and distance sensors and sensing system for elderly people. (2021) - Mohan, C.; Verma, H.K.
Abstract: Elderly people need either a caretaker or a cart to carry their belongings in and around their house or to/from nearby places, like a shopping mall, bus stop etc. This paper reports the development of a direction-cum-distance sensing system (DDSS) using ultrasonic sensors for a cart to assist elderly people. The DDSS can convert an ordinary assistive cart into a person-following assistive robot cart that would follow its user/target. Instead of using infrared or vision-based tracking systems for sensing direction and distance, as reported by other researchers, the DDSS reported here uses ultrasonic beam/pulses. The DDSS integrates the two tasks of finding the direction and measuring the distance in a single unit. For finding the direction of the target (user), an ultrasonic transmitter is placed on the back of the target, whereas two ultrasonic sensors are placed on the front of the cart. The distance of the target from the cart is measured using the classical technique of measuring the time taken by ultrasonic pulses to travel from the cart up to the target and back from the target to the cart after its reflection from the target. Performance of the DDSS in direction mode has been evaluated experimentally, which is very gratifying. Since the DDSS works with ultrasonic beam/pulses, the assistive robot cart can work not only indoor but also outdoor (where infrared emissions from the sun and other sources may cause mal-operation of infrared-based tracking systems) and in low-visibility areas (where camera-based tracking systems may fail to work). The new DDSS has additional advantages of simplicity, ready availability of components and low cost. Some suggestions for further work are included in the last section of the paper.